2006
DOI: 10.3892/or.15.2.449
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell dissemination in colon cancer does not predict extrahepatic recurrence in patients undergoing surgery for hepatic metastases

Abstract: Abstract. Patients undergoing resection of hepatic metastases of colorectal cancer have a high risk of extrahepatic recurrence, most likely caused by early tumor cell dissemination or the manipulation of liver tumors during surgical resection. Using immunocytochemistry, we studied 47 patients for cytokeratin (CK)-positive (+) cells in: a) bone marrow (BM) samples to determine whether tumor cell dissemination had already occurred before surgery; and b) blood samples directly taken from the hepatic vein before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
(25 reference statements)
0
14
2
1
Order By: Relevance
“…Using an immunohistochemical labelling method, Hansen and colleagues found that tumour cells were detectable in the peripheral blood of 26% of surgical patients at the time of tumour surgery [29]. There is, however, debate about whether such circulating tumour cells are of pathological significance [30][31][32]. Schoppmeyer in 2006 [32] using a similar immunohistochemical labelling method to ours, prospectively studied 47 patients with colonic cancer before and during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an immunohistochemical labelling method, Hansen and colleagues found that tumour cells were detectable in the peripheral blood of 26% of surgical patients at the time of tumour surgery [29]. There is, however, debate about whether such circulating tumour cells are of pathological significance [30][31][32]. Schoppmeyer in 2006 [32] using a similar immunohistochemical labelling method to ours, prospectively studied 47 patients with colonic cancer before and during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, debate about whether such circulating tumour cells are of pathological significance [30][31][32]. Schoppmeyer in 2006 [32] using a similar immunohistochemical labelling method to ours, prospectively studied 47 patients with colonic cancer before and during surgery. Cytokeratin-labelled (CK+) cells were detected in the bone marrow of 26 patients (55%) and in blood samples of 14 patients (30%) before surgery and 11 patients (23%) during surgery with a median detection rate of 1 (range, 1-14) CK+ cell per 4 · 10 6 mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…145,152 In contrast, 3 other reports, mostly on smaller patient cohorts, could not detect any association between prognostic factors and the presence of DTC. 146,147,153 To date, CK20 is the most commonly used marker in RT-PCR analyses of BM from CRC patients (Table II), with more than 10 studies published so far. However, only in 3 studies the number of investigated patients was larger than 100 with DTC detection rates of 11-35%.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…A similar result was published by Wind et al for the respective type of operative procedures, revealing that the cumulative percentage of samples containing CTCs was significantly higher during open surgery as compared to the laparoscopic approach (Wind et al, 2009). However, dissemination of CK + cells during surgery of hepatic metastases, a frequent event in colon cancer patients, did not predict extrahepatic recurrence (Schoppmeyer et al, 2006, Koch et al, 2007. In conclusion, CTCs seem to be generated during surgery; however, their significance for the occurrence of relapses is not clear.…”
Section: Surgery and Tumor Cell Disseminationmentioning
confidence: 81%